EFEKTIVITAS MODEL PEMBELAJARAN TUTOR SEBAYA DENGAN PENGGUNAAN LKS TERHADAP HASIL BELAJAR SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI KELILING DAN LUAS LINGKARAN - Bustan, Ariestha Widyastuty; Samsi, Hasan; Ruhama, Mustafa A. H (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2019)
This research is an experimental research which aims to determine the effectiveness of peer tutoring learning models with the use of LKS on student learning outcomes in solving the story problems in the material around and the area of ​​the circle. The population in this study were all eighth grade students of SMP Negeri 1 Kota Ternate and samples that were randomly taken were class VIIIA students as an experimental class which amounted to 27 students and class VIIIB as a control class totaling 30 students. Data collection is done through tests of student learning outcomes with 5 items as instruments that have been validated by the validator. The analysis of the data used is 5-scale PAP, homogeneity test, normality test, the Mann-Whitney test and hypothesis test. The results of the calculation of the initial homogeneity test obtained F count = 1.29 less than Ftable = 1.90, then the two data are homogeneous. In the normality test the final test data is obtained χ2 count> tabel2 tables or 9.90> 7.82 for the experimental class and χ2 count> χ2 tables or 10.56> 7.82 for the control class, meaning that the two group data are not normally distributed, so used non parametric statistical tests. The non parametric test used is the Mann-Whitney test, from the calculation results obtained by Zhitung = -4.14 with Ztable = ± 1.96 at a significant level () = 0.05, Accept H0 if -Zt ≤ ZH ≤ + Zt and Reject H0 if ZH> Zt or ZH <-Zt. Because ZH <Zt (-4.14 <-1,96), then H0 is rejected and H1 is accepted, meaning that there are differences in student learning outcomes between the experimental class and the control class in class VII students of SMP Negeri 1 Ternate City. Thus, there are differences in learning outcomes in class VIII students of SMP Negeri 1 Kota Ternate who use peer tutoring learning models with the use of LKS and those who do not use the learning model. Based on the mean, level of mastery obtained by the experimental class and the control class, as well as student activities and responses to peer tutoring learning models with the use of LKS, it can be concluded that the application of peer tutoring learning models with the use of effective LKS to improve student learning outcomes material around and area of ​​circle